The use of muscle near-infrared spectroscopy (NIRS) to assess the aerobic training loads of world-class rowers - Klusiewicz, A.; Rebis, K.; Ozimek, M.; Czaplicki, A. (Biology of Sport, 2021)
The objectives of this study were (1) to characterize the changes in oxygenation derived from muscle near-infrared spectroscopy (NIRS) during aerobic constant-load exercise with intensities close to Maximal Lactate Steady-State (MLSS) and (2) to establish reference values in the world-class rowers, for such workload often included in rowing training programs. Eight senior world-class rowers performed an incremental progressive submaximal exercise test and a 30-minute test on a rowing ergometer. The power corresponding to intensive aerobic training (84±1% of the anaerobic threshold) was adopted as an exercise load in the 30-minute test. The NIRS device was fixed on the vastus lateralis muscle which was active during rowing to record muscle O2 saturation (SmO2) and total hemoglobin concentration (THb) at rest and during exercise. Statistically significant increments in blood lactate (LA) and heart rate (HR) were observed, with 1.18±0.61 mmol/l and 10±5 beats/ min, respectively, in 30th minute compared to 10th minute in 30-minute test. SmO2 decreased significantly by 2.9±1.4%, whereas THb did not change. The examinations may suggested the low diagnostic value of THb in constant-load exercise. In each subject, SmO2 was gradually reduced during the intense aerobic exercise. During workload close to MLSS, the SmO2 of the vastus lateralis ranged from 14.0±3.13 to 11.1±2.81% in 10 and 30 minutes respectively, with a reduction in muscle oxygenation (?SmO2) exceeding 50%. The non-invasive nature of the NIRS measurement and the continuous monitoring of SmO2 values are useful in the practice of monitoring training in terms of aerobic training loads.